A&T Burkina Faso Maternal Nutrition Endline Survey 2021: Health Facility - International Food Policy Research Institute (International Food Policy Research Institute, 2023)
Alive & Thrive (A&T) is an initiative that supports the scaling up of nutrition interventions to save lives, prevent illnesses, and contribute to healthy growth and development through improved maternal nutrition and infant and young child feeding practices. In Burkina Faso, A&T developed and tested an intensive package of maternal nutrition interventions to be integrated into existing ANC services delivered through government health facilities. These included intensified counseling and support on dietary diversity and quality during pregnancy, iron-folic acid (IFA) supplements consumption, importance of ANC and increasing the number of visits, adequate weight-gain monitoring, and early initiation of and exclusive breastfeeding. This dataset is part of a survey that was conducted to gather endline data for the impact evaluation of the interventions. The overall study objective was to evaluate the feasibility of integrating locally relevant maternal nutrition interventions into ANC services provided by the government health system and their impact on diet quality and quantity and utilization of nutrition interventions during pregnancy. Research questions include: 1) What are the program impacts on maternal nutrition practices: (1) consumption of diversified foods and adequate intake of micronutrient, protein and energy compared to recommended intakes; (2) consumption of IFA supplements during pregnancy; and (3) early breastfeeding practices? 2) Can the coverage and utilization of key nutrition interventions (maternal nutrition counseling, weight gain monitoring, distribution of and counseling on IFA supplementation, and breastfeeding counseling) and number of ANC contacts be improved through health system strengthening and nutrition-focused social and behavior change communication (SBCC; interpersonal communication and community mobilization) approaches? 3) What factors influenced integration and strengthening of maternal nutrition interventions into the government ANC service delivery platform? The evaluation used a two-arm cluster-randomized, non-masked trial design, consisting of two cross-sectional surveys at baseline and endline. The unit of randomization was the health and social promotion center (CSPS, Centre de Santé et de Promotion Social in French) catchment area. The endline survey was conducted in January-March 2021 by Agence de Formation de Recherche et d'Expertise en Santé pour l'Afrique (AFRICSanté), the in-country research collaborator for the survey. The endline survey included the following: 1) Pregnant women questionnaire, 2) Recently delivered women questionnaire, 3) Husbands of recently delivered women questionnaire, 4) Nurse-midwife questionnaire, 5) Community health agents (agent de santé communautaire, ASBCs) questionnaire, 6) Health facility observation checklist, and 7) ANC observation and exit interview. The health facility observation checklists were conducted using pretested, structured questionnaires. Information was collected on condition of the facility infrastructure, service readiness, services provided by the facility, human resources, and ANC monitoring system.